2021
DOI: 10.1038/s41396-021-00909-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonnutritive sweeteners can promote the dissemination of antibiotic resistance through conjugative gene transfer

Abstract: Antimicrobial resistance (AMR) poses a worldwide threat to human health and biosecurity. The spread of antibiotic resistance genes (ARGs) via conjugative plasmid transfer is a major contributor to the evolution of this resistance. Although permitted as safe food additives, compounds such as saccharine, sucralose, aspartame, and acesulfame potassium that are commonly used as nonnutritive sweeteners have recently been associated with shifts in the gut microbiota similar to those caused by antibiotics. As antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(132 citation statements)
references
References 54 publications
(65 reference statements)
4
120
0
2
Order By: Relevance
“…Indeed, whilst studies indicate the potential for olfactory responses in Bacillus licheniformis , there is no literature indicating the presence of a sweet taste receptor or sensor in bacteria which could respond to artificial sweeteners [ 50 ]. Instead, there is evidence that sweeteners can cause DNA damage in bacteria, elevate bacterial mutation rate in a dose-dependent manner or ROS production and detoxification, and increase cell membrane permeability [ 51 , 52 , 53 , 54 ]. ROS can modulate the quorum sensing ability of bacteria to sense and respond to their environment [ 55 , 56 ] therefore sweeteners may impact pathogenicity of model gut bacteria in the present study through a ROS-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, whilst studies indicate the potential for olfactory responses in Bacillus licheniformis , there is no literature indicating the presence of a sweet taste receptor or sensor in bacteria which could respond to artificial sweeteners [ 50 ]. Instead, there is evidence that sweeteners can cause DNA damage in bacteria, elevate bacterial mutation rate in a dose-dependent manner or ROS production and detoxification, and increase cell membrane permeability [ 51 , 52 , 53 , 54 ]. ROS can modulate the quorum sensing ability of bacteria to sense and respond to their environment [ 55 , 56 ] therefore sweeteners may impact pathogenicity of model gut bacteria in the present study through a ROS-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, sweeteners (acesulfame, saccharin, and sucralose) have been detected in wastewater, surface water, groundwater, and drinking water systems [ 61 , 62 , 63 ]. More worryingly, artificial sweeteners have been linked to increased horizontal transfer of antimicrobial resistance genes in environmental and clinical settings [ 52 , 54 ]. In addition, increased biofilm formation is believed to cause medical device-associated infections and is closely linked to the antibiotic-resistant bacteria, which is now a widespread public health threat [ 64 , 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we hypothesized that these widely-used food additives [13][14][15] might also contribute to the dissemination of antibiotic resistance among bacteria. Our recent study has demonstrated that the widely-used artificial sweeteners can promote horizontal transfer of ARGs via conjugation [16]. These sweeteners promoted pili formation and increased expression of conjugative transfer-related genes located on the plasmid.…”
Section: Introductionmentioning
confidence: 98%
“…In the Nano&Tet group and the Nano&Ery group, PI uptake was much higher than that in the Tet group and the Ery group, suggesting that the combined impacts significantly decreased the antibiotic resistance of the systems [ 31 , 32 ]. Bacteria can reduce intracellular availability of antibiotics by inhibiting or replacing outer membrane porins and overexpressing efflux pumps.…”
Section: Resultsmentioning
confidence: 99%
“…After washed twice with 0.85% (w/v) NaCl solution, the bacterial suspension was diluted to a cell density with an optical density at 600 nm (OD 600 ) of 0.10±0.02 [ 30 ]. One mL of bacterial suspension was stained with 10 μl of propidium iodide (PI) (1 mg/ml, OMEGA, USA) and incubated in the dark for 8 min before measurement [ 31 , 32 ]. The cell permeability was tested by flow cytometry analysis (FCM, BD FACSCalibur, USA) and PI fluorescent signal was excited by 488 nm.…”
Section: Methodsmentioning
confidence: 99%